Zn/ZnBr2 Catalysed Reaction of Aldehydes with Allylbromide: Synthesis of 2,6-Disubstituted 4-Bromotetrahydropyrans - D. O. Biradar; Y. D. Mane; Y. P. Sarnikar; S. G. Kulkarni; B. V. Subba Reddy; A. Venkat Narsaiah (SynOpen, 2022)
An efficient approach for the one-pot synthesis of 4-bromotetrahydropyrans in a highly diastereoselective manner via the alkynylation followed by Prins cyclisation is described. The method employs aldehydes and allyl bromide as reactants, with a Zn/ZnBr2 catalytic system in CH2Cl2. A variety of 2,6-disubstituted 4-bromotetrahydropyran derivatives were obtained in good yields.